Factor Analysis of Students Difficulty in Early Reading at Elementary School: Analisis Faktor Kesulitan Siswa dalam Membaca Permulaan di Sekolah Dasar - Arifianto, Teguh; Supriyadi, Supriyadi (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to analyze the factors that influence students' difficulty in reading the beginning by taking the object of research at Suko 1 Sidoarjo State Elementary School. While the type of research selected is a case study with 2 subjects. Data was collected through observation, interview, and documentation techniques. Then analyzed using the interactive analysis of the Miles model, namely data condensation, data presentation, drawing conclusions, and data verification. Test the validity of the data using triangulation techniques. The results showed that early reading difficulties were related to omitting words, replacing words, letters, stammering spelling, pronouncing wrong words, and pronouncing patent letters. These difficulties are influenced by four internal factors, namely daily activities, understanding of the material, psychological conditions, and learning motivation. External factors that affect learning difficulties in early reading are the role of the teacher and the family environment.